Metacognition in literacy learning : theory, assessment, instruction, and professional development - Israel, Susan E.; Block, Cathy Collins; Bauserman, Kathryn L.; Kinnucan-Welsch, Kathryn (L. Erlbaum Associates, 2008)
An examination of metacognition in literacy learning. It provides the theoretical foundation that supports the teaching of metacognition; new methods for metacognitive assessment and instruction in literacy contexts at all grade levels; and new information on integrating metacognition into professional development programs.